A Reusable CNT‐Supported Single‐Atom Iron Catalyst for the Highly Efficient Synthesis of C−N Bonds. Issue 20 (18th March 2020) - Ding, Qifeng; Yu, Yang; Huang, Fei; Zhang, Lihui; Zheng, Jian‐Guo; Xu, Mingjie; Baell, Jonathan B.; Huang, He
Abstract: C−N bond formation is regarded as a very useful and fundamental reaction for the synthesis of nitrogen‐containing molecules in both organic and pharmaceutical chemistry. Noble‐metal and homogeneous catalysts have frequently been used for C−N bond formation, however, these catalysts have a number of disadvantages, such as high cost, toxicity, and low atom economy. In this work, a low‐toxic and cheap iron complex (iron ethylene‐1, 2‐diamine) has been loaded onto carbon nanotubes (CNTs) to prepare a heterogeneous single‐atom catalyst (SAC) named Fe‐N x /CNTs. We employed this SAC in the synthesis of C−N bonds for the first time. It was found that Fe‐N x /CNTs is an efficient catalyst for the synthesis of C−N bonds starting from aromatic amines and ketones. Its catalytic performance was excellent, giving yields of up to 96 %, six‐fold higher than the yields obtained with noble‐metal catalysts, such as AuCl3 /CNTs and RhCl3 /CNTs. The catalyst showed efficacy in the reactions of thirteen aromatic amine substrates, without the need for additives, and seventeen enaminones were obtained. High‐angle annular dark‐field scanning transmission electron microscopy in combination with X‐ray absorption spectroscopy revealed that the iron species were well dispersed in the Fe‐N x /CNTs catalyst as single atoms and that Fe‐N x might be the catalytic active species. This Fe‐N x /CNTs catalyst has potential industrial applications as it could be cycled seven times without any significant loss of activity. Abstract : A superior commoner ! A reusable single‐atom catalyst (SAC), Fe‐N x /CNTs, prepared from iron ethylene‐1, 2‐diamine and carbon nanotubes (CNTs), has been used for the construction of C−N bonds. The catalytic performance superior to those of noble‐metal catalysts such as AuCl3 /CNTs and RhCl3 /CNTs. This outstanding performance originates from the introduction of Fe‐N x into the CNTs and the resulting electronic coupling between the iron species and the CNTs.